EFFECT OF PRODUCT QUALITY, PRICES AND PLACES ON PURCHASE DECISIONS - Nur Aeni (Kusuma Negara Business School, 2020)
The purpose of this study was to determine the effect of product quality, price, and place on the purchase decision of Meatballs Ikhtiar. The research method used was quantitative research in the form of a survey. The research sample of 100 consumers Meatballs Tofu Ikhtiar. The data collection method uses a questionnaire. Data analysis techniques using multiple linear regression tests, partial hypothesis testing using t-test and simultaneous test using the F test. The results of this study are that there is a significant influence on product quality on purchasing decisions. There is a significant effect on price decisions. There is a significant influence of place influence on purchasing decisions. There is a significant influence on product quality, price and place simultaneously on the decision. The magnitude of the effect of product quality, price and place simultaneously on purchasing decisions. The conclusion of the study is that there is a significant influence on product quality, price, and place on the purchasing decision of Ikhtiar Meatballs Tofu.